Analysis the Influence of the Information and Communication Industry on GDP Sector and Economic Growth - Sembiring, Baloura; Tanjung, Ahmad Albar; Sukardi, Sukardi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to delve into the influence of the information and communication industry on the economic growth of a country or region. The information and communication industry has become a major driver in the global economic transformation, especially in the rapidly evolving digital era. According to its methodology, this research falls under ex post facto research, examining cause-and-effect relationships. Meanwhile, in terms of data type and analysis, this research is quantitative. This research utilizes the Error Correction Model (ECM) data analysis technique. The results of this research show that the economic growth of Indonesia tends to increase, while the stock prices of information and communication industry companies fluctuate with varying trends of increase and decrease. The information and communication industry has been proven to influence the economic growth of Indonesia positively and significantly.